Strategi Penanggulangan Kemiskinan Melalui Pemberdayaan Usaha Mikro, Kecil dan Menengah (UMKM) - Putriana Putriana (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
One indicator of the succsess of economic development or government of a county is poor because of the reduced essentially a development is to improve the welfare of society as fair and eguitable. Development objectives are closely related to efforts to reduce poverty and income inequality. Poverty in Riau province is also one of the problems faced in the successful development when viewed from the side of the emerging economies because of the inequality in the ownership of the resourcesurces that give rise to in equality in income distribution, the difference in the quality of human resources and differences in access to capital and low employment there. An effort was make in tackling poverty by promoting economic empowerment of people throught the Micro, Small and Medium Enterprises (SMEs). SMEs have strategic role in national economic development that can enhance economic growth, employment and the distribution of development outcomes. A very important role csn be seen from the perspective of employment and income to the poor, income distribution, proverty reduction and economic development. The main objective is the empowerment of SMEs to enchance productivity of SMEs, promote the effectiveness of programs and activities related to the empowerment of SMEs. Empowerment and development of SMEs in tackling poverty is to provide access to the poor to be able to engage in business and active in productive business activities and promote enterpreneurship, especially among the poor or disadvantaged areas.